2017
DOI: 10.1038/s41598-017-15060-x
|View full text |Cite
|
Sign up to set email alerts
|

Pd supported on carbon containing nickel, nitrogen and sulfur for ethanol electrooxidation

Abstract: Fuel cells are widely recognized as very attractive devices to obtain directly electric energy through an electrochemical reaction between anode and cathode 1 . Among the power sources, direct methanol fuel cells (DMFCs) have been extensively investigated and proposed to be used as mobile applications 2 . Compared to methanol, ethanol is a promising alternative fuel with less toxicity. Direct ethanol fuel cells (DEFCs) have been extensive studied by many research groups [3][4][5][6] . As emerging technologies,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 43 publications
3
18
0
Order By: Relevance
“…Unlike the results shown in Table S1, no Si is found, and the element ratios are different because XPS is a general surface analysis tool, while its penetration depth is rather limited in comparison with EDS. The C 1s peaks of the three samples shown in 28,29 The high content of graphitic C is in agreement with the XRD and Figure 2b,c. The ratios of different types of carbon are shown in Table S4.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…Unlike the results shown in Table S1, no Si is found, and the element ratios are different because XPS is a general surface analysis tool, while its penetration depth is rather limited in comparison with EDS. The C 1s peaks of the three samples shown in 28,29 The high content of graphitic C is in agreement with the XRD and Figure 2b,c. The ratios of different types of carbon are shown in Table S4.…”
supporting
confidence: 85%
“…Both the EDS (Table S1) and XPS results (Figure S7a and Table S3) showed that the mesoporous carbon substrate is nitrogen-doped, with the atomic ratio ranging from 1.1% to 3.6%. The N 1s core spectra (Figure S7c) show that the element N exists in the forms of pyridinic N (398 eV), pyrrolic N (400 eV), graphitic N (401 eV), and oxidized N (403 eV). The graphitic N could improve the electrical conductivity of the carbon substrate, while pyridinic N and pyrrolic N could serve as metal-coordination sites. It is widely accepted that graphitic-N could increase the limiting current density, while pyridinic-N could improve the onset potential for the OER .…”
mentioning
confidence: 99%
“…This is relevant to study and optimize the electrocatalytic activity and stability for the EOR [33] but also other alcohols oxidation [57,63,64] or alternative reactions where Pd is key [65]. The effect of support [66], loading [58], different electrochemical testing protocols including an "activation procedure" or longer tests [21,52], different electrolytes [67], the effect of adding surfactant to the catalyst [20], and ink composition [68] are all important parameters to understand in order to rationally design improved supported catalysts [37]. With the simple systems and approach presented, all these parameters can be systematically addressed and studied in greater detail.…”
Section: Discussionmentioning
confidence: 99%
“…In Figure 3B, the intense peaks appeared at 1343.9 and 1579.2 cm À1 represent the D-band and G-band, respectively. 46 The D-band is the result of a defective graphitic structure, and the G-band represents highly ordered lattice of bonded carbon atoms. 47 The additional peaks at the wavelengths of ~520 and 1082 cm À1 correspond to SiO 2 and Si of silicon substrate, respectively, because the sample powder was placed on the silicon substrate.…”
Section: Resultsmentioning
confidence: 99%